2011
DOI: 10.1158/1940-6207.capr-10-0397
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Prostate Cancer-Specific Survival of Men with BRCA2 Mutations from Multiple Breast Cancer Families

Abstract: The role of a germ-line BRCA2 mutation in the development of prostate cancer is established, but the clinical presentation linked to outcome for this group of men has not been well described.A total of 148 men from 1,423 families were ascertained from the kConFab consortium. Each participant met the following criteria: (i) a verified case of prostate cancer; (ii) confirmed as either a carrier or noncarrier of a family-specific BRCA pathogenic mutation; (iii) comprehensive clinical and treatment data were avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 38 publications
(51 reference statements)
7
75
1
2
Order By: Relevance
“…We have not seen differences in age at diagnosis as previously reported by others. 65,84,89,91 This contradicts Tryggvadottir's observations, 64 but our study 63 did not include any patients with the Icelandic founder mutation BRCA2 999del5, and we cannot exclude that some mutations are associated with younger age at diagnosis. BRCA1 and BRCA2 carriers had a higher incidence of poorly differentiated tumours, presented with larger tumours and a higher incidence of node involvement and distant metastasis.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…We have not seen differences in age at diagnosis as previously reported by others. 65,84,89,91 This contradicts Tryggvadottir's observations, 64 but our study 63 did not include any patients with the Icelandic founder mutation BRCA2 999del5, and we cannot exclude that some mutations are associated with younger age at diagnosis. BRCA1 and BRCA2 carriers had a higher incidence of poorly differentiated tumours, presented with larger tumours and a higher incidence of node involvement and distant metastasis.…”
Section: Discussioncontrasting
confidence: 62%
“…Carriers had a median OS of only 4.8 years compared with 8.5 years for the noncarriers. More recently, Thorne et al 89 reported the analysis of the outcome of PCa in 40 BRCA2 mutation carriers compared with 97 BRCA wild-type patients. Non-carriers belonged to families with a history of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There remains debate about whether there is an increased risk of PrCa associated with BRCA1 mutations, with some studies reporting no increased risk to those reporting a 1.8-3.75 fold increased risk (Thompson et al, 2002;Leongamornlert et al, 2012;Moran et al, 2012). A number of studies have reported that BRCA2 mutation carriers have more aggressive disease, suggested by their younger age at diagnosis, higher rates of lymph node involvement and distant metastasis at diagnosis, and higher mortality rates compared with non-carriers (Tryggvadóttir et al, 2007;Mitra et al, 2008;Edwards et al, 2010;Gallagher et al, 2010;Thorne et al, 2011;Castro et al, 2013). There is increasing evidence that BRCA1 mutation carriers may also harbour more aggressive disease (Giusti et al, 2003;Gallagher et al, 2010;Castro et al, 2013).…”
mentioning
confidence: 99%
“…12 Other similar studies corroborate these findings. [13][14][15][16] Until recently, reports on the screening outcomes of male BRCA1/2 carriers have been scarce and often limited to specific founder mutations studied in a select population. In 2005, our centre evaluated the utility of targeted screening for detecting prostate cancer in BRCA1/2 carriers.…”
Section: E783mentioning
confidence: 99%
“…[11][12][13][14][15][16][21][22][23][24] This study sought to understand the screening characteristics, cancer detection, and treatment outcomes for mutation carriers as compared to men with a family history of prostate cancer to understand the most appropriate screening and treatment regimens for these high-risk patients.…”
Section: Cuaj • November-december 2014 • Volume 8 Issues 11-12 E786mentioning
confidence: 99%